2008
DOI: 10.1186/1475-2859-7-16
|View full text |Cite
|
Sign up to set email alerts
|

A genomic search approach to identify esterases in Propionibacterium freudenreichii involved in the formation of flavour in Emmental cheese

Abstract: Background: Lipolysis is an important process of cheese ripening that contributes to the formation of flavour. Propionibacterium freudenreichii is the main agent of lipolysis in Emmental cheese; however, the enzymes involved produced by this species have not yet been identified. Lipolysis is performed by esterases (carboxylic ester hydrolases, EC 3.1.1.-) which are able to hydrolyse acylglycerols bearing short, medium and long chain fatty acids. The genome sequence of P. freudenreichii type strain CIP103027 T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 43 publications
0
16
1
Order By: Relevance
“…Here, an iterative strategy was used by integrating heterogeneous localization predictors of lipoprotein-, Tat-, or Sec-dependent signal peptides and transmembrane domains. We showed that one esterase, PF#279, was predicted to be secreted in the medium, and one putative esterase, PF#774, was predicted to be anchored in the plasma membrane, in agreement with previous suggestions made using SignalP as a unique tool (7). In contrast, unclear results were previously found for another esterase, PF#1509, which was clearly predicted as intracellular in the present study.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Here, an iterative strategy was used by integrating heterogeneous localization predictors of lipoprotein-, Tat-, or Sec-dependent signal peptides and transmembrane domains. We showed that one esterase, PF#279, was predicted to be secreted in the medium, and one putative esterase, PF#774, was predicted to be anchored in the plasma membrane, in agreement with previous suggestions made using SignalP as a unique tool (7). In contrast, unclear results were previously found for another esterase, PF#1509, which was clearly predicted as intracellular in the present study.…”
Section: Discussioncontrasting
confidence: 54%
“…However, since the absence of cell lysis was not strictly demonstrated in the latter studies, the esterase activity observed in culture supernatant may have resulted from the release of intracellular enzyme(s) from lysed cells, as previously stressed by Collins et al (2). Twelve putative esterases have been recently identified from the genome sequence of P. freudenreichii CIRM1 T (7). In the present study, we aimed to identify the most probable esterase(s) involved in lipolysis in Emmental cheese, i.e., the esterases that fulfill the following conditions: (i) to be expressed in P. freudenreichii, (ii) to be surface exposed or secreted, and (iii) to be active on milk fat.…”
mentioning
confidence: 89%
“…Two esterases, one extracellular and other surface-exposed seem to be involved in lipolysis of milk glycerides [63,64]. Furthermore, ten intracellular esterases were found in the P. freudenreichii genome that could be involved in the synthesis of the volatile esters associated with the fruity flavor of cheese [65].…”
Section: Dairy Starters For Swiss-type Cheeses and Other Productsmentioning
confidence: 99%
“…Much knowledge has been accumulated about diverging genes and converging evolution (Pichersky et al 2006), flavour genes and enzymes (Dherbecourt et al 2008). The toolbox of molecular biology and the volume of sequence databases is ever-increasing (Matsuta et al 2009).…”
Section: Resultsmentioning
confidence: 99%